Implementing Evidence-Based Practice Education in Social Work: A Transdisciplinary Approach. (July 2013) - Bellamy, Jennifer L.; Mullen, Edward J.; Satterfield, Jason M.; Newhouse, Robin P.; Ferguson, Molly; Brownson, Ross C.; Spring, Bonnie
Evidence based practice (EBP) is reflected in social work publications, accreditation standards, research, and funding opportunities. However, implementing EBP in social work practice and education has proven challenging, highlighting the need for additional resources. This paper describes the Transdisciplinary Model of EBP, a model based on advances in EBP across health disciplines including social work and its application to the development of an online EBP training portal. Utility of the Transdiciplinary Model and a training portal for social work education is discussed. Also included is a description of the training modules, the Council on Social Work Education Educational Policy and Accreditation Standards competencies reflected in the modules, and a case example using the modules in a master s of social work course.